Immunomudulatory effects of hydroalcoholic extract of Hypericum perforatum - Seyyed Meysam Abtahi Froushani; Hadi Esmaili gouvarchin Galee; Mahsa Khamisabadi; Bita Lotfallahzade (Mashhad University of Medical Sciences, 2014)
Objective: Hypericum perforatum (St. John's Wort) has long been used in traditional medicine to treat a variety of internal and external ailments. The present study was done to evaluate the immumodulatory potentials of the hydroalcoholic extract of H. perforatum. Materials and Methods: Twenty male BALB/c-mice were randomly allocated in two equal groups and immunized with sheep red blood cells (SRBCs) and complete Freund's adjuvant. Mice in the treatment group orally received hydroalcoholic extract of H. perforatum (110 mg/Kg daily) from the beginning of the study  which continued for 2 weeks. Results: The data indicated a significant increase in the level of anti-SRBC antibody and simultaneously a significant decrease in the level of cellular immunity, an enhancement in foot pad thickness, in treatment group compared to control group. The level of the respiratory burst in phagocytic cells and the level of lymphocyte proliferation in splenocytes were significantly decreased in the treatment group compared to control group. Moreover, extract caused a significant reduction in the production of pro-inflammatory IL-17 as well as IFN-γ, parallel to increasing the level of IL-6. Conclusions: The hydroalcoholicextract of H. perforatum may be used as a natural source for treatment of immunopathologic conditions.